Building Consumer Perception and Satisfaction Through Sharia Compliance and Security of Sharia Digital Banking - Muhammad Khaerul Muttaqien; Tajudin Mas’ud; Hamli Syaifullah; Laila Yumna; Ahmad Tibrizi Soni Wicaksono (LP2M IAIN Palopo, 2026)
The rapid development of financial technology has transformed banking services, including Islamic banking, which strives to meet Muslims’ financial needs in accordance with Islamic principles. This study aims to examine the influence of Sharia compliance and system security on consumer perceptions and satisfaction with Islamic digital banking services. Using a quantitative approach, data were collected through an online survey of 103 Muslim Islamic bank customers in Greater Jakarta, Indonesia. PLS-SEM analysis showed that Sharia compliance and security significantly influenced consumer perceptions (R² = 0.826), whereas perceptions and security contributed to consumer satisfaction (R² = 0.668). The results of the hypothesis test indicate that Sharia compliance has a positive and significant effect on perceptions but not directly on consumer satisfaction. Perception mediates the relationship between Shariah compliance and consumer satisfaction. Security significantly influences consumer perception and satisfaction. This study emphasizes the importance of integrating Sharia compliance and security to improve customer perceptions and satisfaction with Islamic digital banking.